Pedophilia and Exhibitionism - Mohr, Johann W. (Book collections on Project MUSE., 1964)
The primary purpose of this book is to explore the nature of two forms of sexual behaviour which represent the majority of sexual offences coming to the attention of the courts. Special emphasis is given to the social significance of the deviant behaviour. The material presented has emerged primarily from empirical study and research on cases referred to the Forensic Clinic of the Toronto Psychiatric Hospital, established by the Government of Ontario in affiliation with the Department of Psychiatry of the University of Toronto. The Clinic was established specifically to assist the courts in the assessment and treatment of offenders. The choice of exhibitionism and pedophilia for consideration was made on purely quantitative grounds, and quantitative considerations remained a leading factor throughout the study. The bizarre and exotic phenomena of sexual behaviour too frequently overshadow the far greater amount of human misery which can be observed daily in our lower courts. All too often the problems of the sexual offender are seen in terms of isolated but highly publicized cases of atrocities with the result that the minor sex offender (who is by far in the majority) tends to be seen as a potential fiend and maniac. In the absence of a clear picture of the natural history of the various sexual deviations and resulting offences, predictions of the subsequent behaviour of an offender are at best tenuous. In reviewing the literature on pedophilia and exhibitionism, the authors found no systemic account of pedophilia, and only one book specifically devoted to exhibitionism. It therefore became necessary to expand their own researches into a handbook on the sexual offences arising out of the two deviations. Comparative data from the literature has been incorporated. The organization of this material posed many problems because of the diversity of definitions, samples, and classifications used in various studies, and this diversity reflects the great need for investigation of the subject if diagnosis, sentencing, and treatment are to be soundly based. In his Foreword, Professor Kenneth G. Gray points to the usefulness of this study in many areas: "Psychiatrists will find a great deal of information about selection of cases for treatment. The prognosis for sex offenders is generally good but it is better from some categories of offenders than others. With rare exceptions, the sex offender is not mentally ill or mentally defective except with regard to his sexual deviation ... Judges and magistrates will find here information that is of value in sentencing a sexual offender. Research has produced data which provide a reasonably accurate prediction about the likelihood of recurrence ... Social workers and educators will be particularly interested in the description of sexual molestation of young children. They will be able to convey such information to parents whose child has been assaulted and will be better able to assess the effects on the child and to deal with them."